Belt-sulfur mobilization as a crucial mechanistic feature shared between the vanadium and molybdenum nitrogenases - Lee, Chi Chung; Chatterjee, Kuntal; Yano, Junko; Kern, Jan; Stiebritz, Martin; Ribbe, Markus W.; Hu, Yilin (Chem Catalysis, 2025)
Nitrogenase catalyzes the reduction of N2 to NH3 at its active site cofactor. Recent studies of the “conventional” Mo-nitrogenase suggest a plausible involvement of all cofactor belt-S sites in catalysis. Here, we use analytical, enzymatic, and spectroscopic methods to demonstrate the same dynamic belt-S mobilization by the “alternative” V-nitrogenase during catalysis. Our results point to belt-S turnover as a common catalytic feature of the homologous Mo- and V-nitrogenases while identifying an activated but N2-free conformation of the V-nitrogenase that holds great potential for facilitating future mechanistic explorations of the intriguing nitrogenase enzyme.
CRIS-Team Scopus Importer:2025-05-09
Keywords: ammonia formation; belt-sulfur mobilization; catalysis; cofactor; deuterium incorporation; nitrogenase; SDG9: Industry; innovation; and infrastructure